Qualidade e análise sensorial de filés de peitos (Pectoralis major) de frangos comerciais submetidos a diferentes tempos de exposição ao calor - Gotardo, Luciana Ruggeri Menezes (2016)
The objective of this study was to investigate the effects of different times of heat exposure on the quality and sensorial parameters of broilers (Pectoralis major) of broilers of the Cobb® and Hubbard Flex® strains. A total of 560 Hubbard Flex® and 560 Cobb® strains broilers were housed in a completely randomized design in four thermal environments. The broilers of the control environment were created according to thermal recommendation for the strain. On the other hand, the animals from the other environments were submitted to heat stress of 1h, 2h and 3h daily, respectively, starting at 11h00 from the 14th day of age. The variables pH 90 minutes (pH 90 min), 24 hours (pH 24 h) post mortem; Color (obtained by luminosity L*, a* and b*), drip loss 24 (DL 24 h) and 72 hours (DL72 h); Shearing force (FC) and acceptance and preference tests were analyzed. The data were submitted to analysis of variance and the means were compared by the Tukey test at 5%. Heat cyclic stress did not influence pH 90 min, pH 24 h, L*, a* and b*, DL 24 h, DL 72 h, FC. The Cobb® chicken breast presented higher pH 24 h, a* and b* compared to Hubbard Flex. In sensory evaluation, the evaluators could detect the lighter color fillets in the majority. The overall acceptance was firstly by breast fillet PSE and in the second acceptance test the sample chosen was normal. It was concluded that the daily exposure of the chicken to the heat, for up to three hours, did not influence any of the evaluated parameters. In the Cobb line the chicken breast fillets are more reddish and yellowish and of a higher pH 24 h than the Hubbard strain. The consumer has no parameter of comparison between normal chicken breast and PSE.